The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Addressing decarbonization strategies through a game theory perspective - Elizabeth A. Moore; Karan Bhuwalka; Andy Zhu; Yijia Chen; Panya Tang; Jennifer D. Russell; Randolph Kirchain; Richard Roth (Resources, Conservation and Recycling, 2025)

Using hyperspectral and thermal imagery to monitor stress of Southern California plant species during the 2013–2015 drought - Susan K. Meerdink; Dar A. Roberts; Jennifer Y. King; Keely L. Roth; Paul D. Gader; Kelly K. Caylor (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Structural basis of HydBC modularity and its diversity in anaerobic bacteria - Anuj Kumar; Jennifer Roth; Lena Schmück; Volker Müller; Jan Schuller (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Elucidating the redox-driven sodium pumping mechanism of the ancient Rnf complex - Hyunho Kim; Anuj Kumar; Patricia Saura; Jennifer Roth; Stefan Bohn; Tristan Reif-Trauttmansdorff; Anja Schubert; Volker Müller; Jan M. Schuller; Ville R.I. Kaila (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A functional Wood–Ljungdahl pathway devoid of a formate dehydrogenase in the gut acetogens Blautia wexlerae , Blautia luti and beyond - Raphael Trischler; Jennifer Roth; Matthew T. Sorbara; Xenia Schlegel; Volker Müller (Environmental Microbiology, 2022)
Summary Species of the genus Blautia are typical inhabitants of the human gut and considered as beneficial gut microbes. However, their role in the gut microbiome and their metabolic features are poorly understood. Blautia schinkii was described as an acetogenic bacterium, characterized by a functional Wood–Ljungdahl pathway (WLP) of acetogenesis from H 2 + CO 2 . Here we report that two relatives, Blautia luti and Blautia wexlerae do not grow on H 2 + CO 2 . Inspection of the genome sequence revealed all genes of the WLP except genes encoding a formate dehydrogenase and an electron‐bifurcating hydrogenase. Enzyme assays confirmed this prediction. Accordingly, resting cells neither converted H 2 + CO 2 nor H 2 + HCOOH + CO 2 to acetate. Carbon monoxide is an intermediate of the WLP and substrate for many acetogens. Blautia luti and B . wexlerae had an active CO dehydrogenase and resting cells performed acetogenesis from HCOOH + CO 2 + CO, demonstrating a functional WLP. Bioinformatic analyses revealed that many Blautia strains as well as other gut acetogens lack formate dehydrogenases and hydrogenases. Thus, the use of formate instead of H 2 + CO 2 as an interspecies hydrogen and electron carrier seems to be more common in the gut microbiome.

Role of ingesta particle size in the green turtle grazing strategy, ontogenetic diet shifts, and responses to seagrass declines - Alexandra G. Gulick; Anne B. Meylan; Peter A. Meylan; Kristen M. Hart; Jennifer A. Gray; Gaëlle Roth; Alan B. Bolten; Karen A. Bjorndal (Marine Biology, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Pharmacokinetics in mice implanted with xenografted tumors after intravenous administration of tasidotin (ILX651) or its carboxylate metabolite - Peter L. Bonate; David Beyerlein; Jennifer Crawford; Stephanie Roth; Roy Krumbholz; Steve Schmid (The AAPS Journal, 2007)

Methodological Considerations Regarding the Measurement of Turbulent Fluxes in the Urban Roughness Sublayer: The Role of Scintillometery - Matthias Roth; Jennifer A. Salmond; A. N. V. Satyanarayana (Boundary-Layer Meteorology, 2006)